2019
DOI: 10.5897/ajest2019.2691
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiological risk from the soils of artisanal mining areas of Anka, North West Nigeria

Abstract: Assessment of radiological risk was carried out on twenty soil samples collected from agricultural, mining and mine processing areas in Anka, Zamfara State, North Western Nigeria. The measurement of activity concentration of 226 Ra, 232 Th and 40 K was performed using the gamma-ray spectrometer equipped with a high purity germanium detector. The values of the activity concentration of 226 Ra ranged from 24.69±4.26 to 82.20±15.62 Bqkg -1 , with a mean of 47.06±14.01 Bqkg -1 ; 232 Th ranged from 22.52±3.44 to 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
7
2
Order By: Relevance
“…The average activity concentration of Ra-226, Th-232 and K-40 obtained in this study is higher than that obtained in Nigeria by Mbet et al [12], Ibikunle et al [13] and Oluyide et al [19] in Nigeria and Harb et al [20] in Egypt. The average activity concentration of Ra-226, Th-232 and K-40 from this study are higher than the median values throughout the world according to UNSCEAR [10].…”
Section: Comparison Of Activity Concentration With Previous Studiescontrasting
confidence: 78%
See 4 more Smart Citations
“…The average activity concentration of Ra-226, Th-232 and K-40 obtained in this study is higher than that obtained in Nigeria by Mbet et al [12], Ibikunle et al [13] and Oluyide et al [19] in Nigeria and Harb et al [20] in Egypt. The average activity concentration of Ra-226, Th-232 and K-40 from this study are higher than the median values throughout the world according to UNSCEAR [10].…”
Section: Comparison Of Activity Concentration With Previous Studiescontrasting
confidence: 78%
“…External Hazard Index was below the recommended value of 0.45, Annual effective dose rate was below the recommended public dose limit of 1mSv/y as recommended by ICRP, while Excessive Life Cancer Risk was above the recommended value of 0.29. Comparison of the results of radiological hazard indices with published data from similar investigations in Nigeria shows higher Gamma Absorbed Dose Rates reported by Mbet et al [12] in Anka, Solomon et al [14] in Jos and Shittu et al [17] in FCT Abuja, while lower dose was recorded by Ode et al [16] in Benue and Usikalu et al [18] in Ogun. For the Radium Equivalent Activity, higher values were reported by Mbet et al [12] in Anka, Solomon et al [14] in Jos and Shittu et al [17] in FCT Abuja, while lower values were reported by Ibikunle et al [13] in the South West and Ibrahim et al [3] in Nasarawa.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations